On the genus Berosus Leach (Coleoptera: Hydrophilidae) in the State of Roraima, Brazil: description of three new species and new records - Santana, Larissa; Benetti, Cesar João; Clarkson, Bruno; Pes, Ana Maria (Zootaxa, 2019)
As a contribution to knowledge of the aquatic beetles of the Neotropical Region, the genus Berosus Leach is recorded for the first time from Roraima State in northern Brazil. Three new species are described and illustrated: Berosus illuviosus sp. n., B. parvus sp. n., and B. andreazzei sp. n. In addition, we present a checklist of the Berosus species collected in 26 ponds in the savanna area of the State of Roraima, with 12 new species records for the state, five of which are also new country records for Brazil.